Syntaxonomy of bogs vegetation of Middle Pridnistrov’ya (class Phragmitо-Magnocaricetea, order Phragmitetalia): description of syntaxons, synekology and synhorology (CHORNOMORSKI BOTANICAL JOURNAL, 2013)
Syntaxonomy scheme class Phragmito-Magnocaricetea swamps Middle of Transnistria on the basis of ecological-floristic method was developed. The class consists of 18 associations that relate to 5 unions and 3 orders of magnitude: Phragmitetalia, Nasturtio- Glycerietalia and Magnocaricetalia. The order Phragmitetalia, which communities are common to all types of bogs represents the greatest scientific and practical interest. It is founded of one union – Phragmition communis, which consists of 6 associations. On the basis of own researches syntaxonomy characteristics and coenotic analysis of the identified groups, marked by the peculiarities of community of class was conducted. The association of Phragmitetum communis appeared to be the most widespread presented on all types of bogs. Association Sparganietum erecti was found only in one bog array.
Keywords: vegetation, swamps, Middle Pridnistrov’ya, class Phragmitо-Magnocaricetea.